KERJASAMA PEMERINTAH- SWASTA DALA,M PELAYANAN AIR MINUM DI DKI JAKARTA (TAHUN 2008-2012) - Andrianus Erwin Alfreyno (KENEGARAAN, 2017)
In an effort to improve public services in DKI Jakarta, particularly the services of drinking water, the local Government of DKI Jakarta PAM Jaya has been held in cooperation with private partners (public-private partnership). This partnership was carried out since 1997, namely PT Thames PAM Jaya (TPJ), which later in 2008 changed its name to PT Aetra Air Jakarta to Eastern area of Jakarta, and PT by Palyja PAM Jaya to the West of Jakarta, by the Ciliwung River as its boundary. The research apply qualitative approach. From the results obtained, on technical aspects, although there are technical aspects of the performance improvements before and after collaboration with partners until the end of 2012, compared to the target host is turns out to be the private partners have not been able to meet the targets set cooperation. So even on this aspect of the service, from to three factors, namely: water quality services, administration and performance rates, none of the services that fact in accordance with customer expectations. Compared to before he did in collaboration with private partners, the perceived performance of customers after a partnership, there is a growing tendency to decrease. Keywords: Public Private Partnership